2009
DOI: 10.1517/17425250903228834
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2: the key to chemoresistance in cancer stem cells?

Abstract: Multi-drug chemoresistance remains one of the most common reasons for chemotherapy failure. The membrane transporter protein ABCG2/BCRP1 has been shown in vitro to effectively reduce the intracellular concentrations of several prominent anticancer chemotherapeutic agents such as mitoxantrone and doxorubicin. Intriguingly, cancer stem cells are known to be characterized by multi-drug chemoresistance. Taking into account that the ABCG2(+) subset of tumor cells are often enriched with cells with cancer stem-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 127 publications
0
90
0
Order By: Relevance
“…[45][46][47] Similarly, the expression of ABC transporters including P-gp was detected in B16F10 cells. [48][49][50] Therefore, based on the above information, it can be concluded that in the case of G-II cells, efflux pumps play an active role in mediating their sensitivities to DOX in a drug-concentration dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…[45][46][47] Similarly, the expression of ABC transporters including P-gp was detected in B16F10 cells. [48][49][50] Therefore, based on the above information, it can be concluded that in the case of G-II cells, efflux pumps play an active role in mediating their sensitivities to DOX in a drug-concentration dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…Its role in chemoresistance has also been studied in breast carcinoma, non-small-cell lung carcinoma, oral squamous cell carcinoma and advanced testicular germ cell tumors. 20 Contradictory results have been found regarding its expression in melanoma cell lines. 21,22 Deichmann et al 21 studied 18 melanoma resection specimens and could not demonstrate ABCG2 mRNA upregulation by reverse transcriptase polymerase chain reaction, while Monzani et al 22 found in vitro and in vivo ABCG2 expression in all the cells expressing CD133 by reverse transcriptase polymerase chain reaction and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-8 are autocrine growth factors for MPM. 35,36 Finally, we found reduced levels of the drug transporter ABCG2, a drug efflux pump responsible for multidrug resistance (MDR) of several solid and non-solid tumors 52 ( Fig. 3A) (Fig.…”
Section: Butein Affects the Resistance Of Mpm Cells To Pemetrexedmentioning
confidence: 92%